2018
DOI: 10.19041/apstract/2018/3-4/13
|View full text |Cite
|
Sign up to set email alerts
|

Economic Profitability of Sweet Pepper Production under Different Irrigation Levels and Polyethylene Mulch in a Plastic Greenhouse

Abstract: Field experiment was conducted, during two successive seasons of 2014- 2015 and 2015- 2016, at Dokki protected agricultural site, Giza Governorate, Egypt, to study the profitability of different applied irrigation levels and polyethylene (PE) mulch on plant growth and yield of sweet pepper, (Capsicum annum L.) cv. Godion F1, under plastic house condition. Three irrigation levels (0.50, 0.75 and 1.00) of crop evapotranspiration (ETc), using drip irrigation system and three PE mulch treatments (transparent, blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The effects of various mulches on a variety of plants, including eggplant [248] and tomato [249], have been studied. Abdrabbo et al [24] stated that the plant response to the plastic mulch depends on the plant cultivar, the materials used, and the environmental conditions. Mulch application improved the water status of sweet cherry crops, according to Yin et al [249].…”
Section: Role Of Mulching On Crop Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of various mulches on a variety of plants, including eggplant [248] and tomato [249], have been studied. Abdrabbo et al [24] stated that the plant response to the plastic mulch depends on the plant cultivar, the materials used, and the environmental conditions. Mulch application improved the water status of sweet cherry crops, according to Yin et al [249].…”
Section: Role Of Mulching On Crop Productionmentioning
confidence: 99%
“…The main goals of mulching are to limit evaporation or water erosion [20], boost soil temperature, improve the soil water supply capacity [21,22], and suppress weeds [23]. Mulching causes improvement in crop production, fosters plant growth, and reduces water usage [24,25] as shown in Figure 3. This review compiled information about mulching, different types of mulching materials, water conservation through mulching, and the effects of diverse mulching soil environments on crop growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Mulching's main objectives are to limit weed growth, improve moisture retention, increase soil warming, and decrease water evaporation (Gan et al, 2013). According to studies, mulching can boost crop growth, yields, and water use (Chaudhary et al, 2003;Abdrabbo et al, 2017;Yu et al, 2018;Ali Mozaffari, 2022).…”
Section: The Potential Of Mulching For Sustainable Soil and Water Con...mentioning
confidence: 99%
“…The effects of different mulches on various plants, such as tomatoes and eggplant, have been investigated (Rodan et al, 2020). According to Abdrabbo et al (2017), the reaction of plants to plastic mulch is impacted by the kind of plant materials utilized and the surrounding environment. A study by Yin et al (2012) found that mulching improved sweet cherry crops' water status.…”
Section: Role Of Mulching On Crop Productionmentioning
confidence: 99%
“…Supplemental irrigation is used in more than 40% of the world's food production (Ahmad, 2016). With limited irrigation resources in Egypt and a gradual rise in population, efficient water utilisation through irrigation is becoming increasingly crucial (Abdrabbo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%